The great potential of dhikr as prevention of coronary heart disease: A review - Abdurachman; Luqman Hakim Andira; Andira, Dzulqarnain; Alkaff, Firas Farisi; Weinheimer, Anita Zara; Dewanti, Adinda Tania (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Dhikr is a form of Islamic prayer that involves repeating certain phrases or words to focus on God's presence. This article proposed the management of coronary heart disease (CHD) through changes in individual character through reminiscence. This review aims to provide an overview of current knowledge on how dhikr practice can affect cardiovascular health. We conducted a systematic search across various databases such as PubMed, Google Scholar, and Scopus, utilizing keywords like "dhikr," "coronary heart disease," "cardiovascular health," "stress reduction," and "prayer." Only peer-reviewed articles published between 2014-2023 were eligible for inclusion in this review. Articles were chosen based on their pertinence to the subject matter and their methodological robustness. Several studies have demonstrated that regular dhikr practice can lead to reduced stress levels and improved mental health outcomes. Additionally, there is growing evidence suggesting that dhikr may also play a role in promoting physical health by lowering blood pressure and cholesterol levels. The total number of papers extracted from the initial search with the specific keyword was more than 50. The most relevant papers were selected based on their alignment with the basic theory of CHD, risk factors, mechanisms, and therapeutic approaches. These findings suggest that dhikr could potentially serve as a valuable tool for preventing CHD. However, more research is needed to fully understand the underlying mechanisms behind these effects. Based on the available data, it appears that dhikr has the potential to reduce stress and improve overall health, making it a promising intervention for preventing CHD. Further research is necessary to better elucidate the exact mechanisms through which dhikr exerts its beneficial effects on cardiovascular health.